Application of Continuous Glucose Monitoring for Diabetes Detection - Pan, Mingxi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Diabetes is a serious chronic disease characterized by high blood glucose. The prevalence of diabetes is very high in the whole world. If isn’t monitored and unmanaged, diabetes can lead to many severe health complications such as heart disease, stroke and kidney disease. Implantable continuous glucose monitoring (CGM) system is the current technique for monitoring the concentration of blood glucose for diabetes patients. There were two common types of implantable CGM in the market, which were electrochemical and optical. Electrochemical CGM systems were developed earlier and used in the market. Only one optical CGM system was used in the market, and many others are still in development. However, optical CGM has more benefits for diabetes patients. This research will show how electrochemical and optical work in the CGM system. It will describe the advantages of the optical CGM system, by comparing it with the electrochemical CGM systems. There are two pieces of research about testing the safety and accuracy of the optical CGM system. It would show how optical CGM systems have a high potential in the area of diabetes. Also, it will describe how optical CGM systems have a high possibility of becoming the future trend in CGM systems.